A reception study of AI-translated idioms and proverbs between Arabic and English - Darwish, Noor; Haider, Ahmad; Tannous, Bayan; Rumman, Ronza N. Abu; Alantari, Doaa; Saed, Hadeel; Dagamseh, Mohammed (Research Journal in Advanced Humanities, 2025)
This study investigates the perceptions of students toward the English- Arabic AI-translation of idioms and proverbs. This involves the evaluation of the performance of ChatGPT when translating Jordanian idiomatic expressions and proverbs into English, using a dataset of 100 examples. Drawing on a large-scale sample of 3,000 students from public and private Jordanian universities, the research examines how students engage with AI tools in translation of culturally embedded figurative language. Using a structured 25-item questionnaire, the analysis revealed that participants who frequently encountered idiomatic content and received formal training in translation evaluation demonstrated greater scepticism toward AI’s handling of figurative meaning. Furthermore, while students acknowledged the efficiency and utility of AI tools, a strong preference remained for human translation when dealing with nuanced, culturally rich expressions.  The assessment of GPT’s performance in rendering the idioms showed inconsistency with most renditions relying on literal translation. Figurative renditions and paraphrases were significantly less common. This implies moderate or limited linguistic ability and cultural sensitivity. These findings can benefit AI developers, linguists, and subtitlers by showcasing some current shortcomings in AI translation.